Bridging Policy, Technology, and Teacher Competence: Digital Evaluation of the PPG Program through SPACE LMS at UIN Sunan Ampel Surabaya - Assegaf, Abd Rachman; Bakar, M. Yunus Abu; Syamsuddin, Muh. (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to evaluate the implementation of the Teacher Professional Education (Pendidikan Profesi Guru – PPG) program at UIN Sunan Ampel Surabaya, which has adopted the Sistem Pembelajaran Agama Cara Elektronik (SPACE) as its Learning Management System (LMS). It seeks to analyze policy frameworks, delivery models, and participant experiences to identify strengths, weaknesses, and strategic opportunities for improving teacher professionalism in Indonesia. Design/methods/approach – The research employed an evaluation design with a prescriptive (normative) analysis approach, combining empirical data with theoretical and policy review. Data were collected from 178 in-service PPG participants through documentation, semi-structured interviews, observation of LMS activities, and online questionnaires. Analysis followed the Miles and Huberman interactive model, encompassing data reduction, display, and conclusion drawing. Findings – Results indicate that the integration of structured academic and administrative policies, Recognition of Prior Learning (RPL) for 24 of 36 credits, and targeted capacity-building through induction programs contributed to a high national pass rate in the Ujian Pengetahuan (UP). Participants favored the fully online format (92.2%) for its flexibility, cost efficiency, and work–study balance, though some suggested blended learning for practical teaching simulations. Challenges include heavy workload, program duration, and accessibility issues for teachers in remote areas. LMS SPACE proved effective for content delivery and assessment but requires enhanced preparatory strategies for high-stakes evaluations. Research implications – The study highlights the need for a balanced hybrid model, aligning online efficiency with selective face-to-face engagement. Policy recommendations include workload redistribution, flexible scheduling, expanded access for non-permanent teachers, and stronger integration between PPG training and school or madrasah practices. These insights can inform national strategies for scaling and refining digital teacher professional development programs in Indonesia.